Does hierarchical culture matter? Moderating organizational learning and job satisfaction among Indonesian civil servants - Aziza, Meilda Aulia; Etikariena, Arum (Faculty of Psychology, Universitas Diponegoro, 2025)
Background: Job satisfaction among civil servants is crucial in improving their public services. Job satisfaction could be enhanced by organizational learning. However, hierarchical cultures can have a positive influence on these processes. Therefore, it is crucial to examine the role of hierarchical culture in shaping the effectiveness of organizational learning to improve job satisfaction.Purpose: This study examines the moderating role of hierarchical culture in the relationship between organizational learning and job satisfaction among civil servants.Method: 203 civil servants participated in an online survey using the Organizational Learning Scale (α=0.90), the Job Satisfaction Scale (α=0.94), and the Hierarchical Culture Scale (α=0.78). Data analysis was conducted using PROCESS.Findings: The results show that organizational learning has a positive and significant relationship with job satisfaction (b = 0.4829, t = 4.3755, p < 0.001). However, the moderating role of hierarchical culture in the relationship between organizational learning and job satisfaction is not significant (b = -0.0380, t = -1.4777, p > 0.005).Implication: This suggests that hierarchical culture neither strengthens nor weakens the relationship between organizational learning and job satisfaction. Internal factors are the primary determinants of job satisfaction for civil servants, regardless of the hierarchical culture in government institutions.